The justifications and legal framework for liberalising intra-OIC trade - Ahamat, Haniff (Statistical Economic and Social Research and Training Centre for Islamic Countries (SESRIC), 2009)
This paper examines the justifications and legal framework for the liberalisation of intra-OIC trade. Before these factors are examined, this paper finds that intra-OIC trade is still low in volume and in proportion if compared to other trade systems. Intra-OIC trade is also concentrated in few OIC Member States and in certain types of products. These findings inform the discussions on the justifications of intra-OIC trade liberalisation and this paper finds that due to the economic conditions prevailing in most OIC Member States it is highly likely that such liberalisation results in trade diversion. Thus shallow integration was preferred by economists so that the OIC 'region' will still be open to flows of goods to and from non-OIC countries. This paper finds that the legal framework for intra-OIC trade liberalisation i.e. the TPS-OIC regime operates according to these principles despite its poor enforcement. However, this paper also finds that there are wider considerations that may require the TPS-OIC regime to balance between minimising the chance of trade diversion and improving the unfavourable economic and trade structures that prevail in most OIC Member States.